Virtual channel model for distributed video coding accounting for quantization noise - Ming YIN; Shu-ting CAI; Yun XIE; Yun ZHANG (Tongxin xuebao)
Due to the inaccuracy model on describing the virtual channel with Laplacian,the rate-distortion performance of distributed video coding is relatively low.The quantization noise will be taken into account for online modeling at the decoder.Further,the dependency among original frames was exploited for estimating the model parameter.Thus,a novel virtual channel model for pixel-domain Wyner-Ziv(PDWZ)coding was proposed.The experimental results show that the proposed model can character the statistics of virtual channel more accurately and the performance of PDWZ based on the proposed model outperforms the one based on Laplacian.